2006
DOI: 10.1103/physrevlett.97.144503
|View full text |Cite
|
Sign up to set email alerts
|

Breakup of Air Bubbles in Water: Memory and Breakdown of Cylindrical Symmetry

Abstract: Using high-speed video, we have studied air bubbles detaching from an underwater nozzle. As a bubble distorts, it forms a thin neck which develops a singular shape as it pinches off. As in other singularities, the minimum neck radius scales with the time until breakup. However, because the air-water interfacial tension does not drive breakup, even small initial cylindrical asymmetries are preserved throughout the collapse. This novel, non-universal singularity retains a memory of the nozzle shape, size and til… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
111
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(129 citation statements)
references
References 23 publications
16
111
1
1
Order By: Relevance
“…(typical values found are 0.54 − 0.60) (Burton et al 2005;Thoroddsen et al 2007;Keim et al 2006;Gordillo et al 2005;Bergmann et al 2006Bergmann et al , 2009b and theoretical studies have shown that the exponent indeed has a weak dependence on the logarithm of the remaining collapse time, approximating to 1 2 only asymptotically at the end (Gordillo & Perez-Saborid 2006;Eggers et al 2007;Gekle et al 2009b). Nonetheless, the full theoretical result lies remarkably close to a power law fit over many decades in time.…”
Section: Axisymmetric Radial Dynamicsmentioning
confidence: 81%
See 2 more Smart Citations
“…(typical values found are 0.54 − 0.60) (Burton et al 2005;Thoroddsen et al 2007;Keim et al 2006;Gordillo et al 2005;Bergmann et al 2006Bergmann et al , 2009b and theoretical studies have shown that the exponent indeed has a weak dependence on the logarithm of the remaining collapse time, approximating to 1 2 only asymptotically at the end (Gordillo & Perez-Saborid 2006;Eggers et al 2007;Gekle et al 2009b). Nonetheless, the full theoretical result lies remarkably close to a power law fit over many decades in time.…”
Section: Axisymmetric Radial Dynamicsmentioning
confidence: 81%
“…The first proposed model was a power law where the radius decreased proportionally to the square root of the remaining time until collapse, τ (Longuet- Higgins et al 1991;Oguz & Prosperetti 1993). Subsequent experimental and numerical studies consistently found the behaviour deviated slightly from that 1 2 power law (Burton et al 2005;Gordillo et al 2005;Keim et al 2006;Bergmann et al 2006;Thoroddsen et al 2007;Bergmann et al 2009b), generating doubts and starting a controversy about the universality of the phenomenon. Gordillo & Perez-Saborid (2006) and Eggers et al (2007) theoretically showed how the power law varies weakly as a function of τ due to a logarithmic correction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of satellite drops and the description of the latest instants prior to pinch-off ͑see the review by Eggers 4 ͒, or the transition from the socalled jetting regime to the dripping regime, 5,6 are details extensively reported in the literature. However, although the generation of bubbles is a phenomenon as common as the drop formation, and of great relevance in a large number of industrial processes, our knowledge of the bubble formation process is still far from being fully complete despite the recent advances in the analytical and experimental description of the bubble pinch-off at low [7][8][9] and high [9][10][11][12][13] Reynolds numbers. For example, the most studied geometry, due its simplicity and importance in many chemical engineering applications, is the growth and subsequent pinch-off of a bubble from an orifice, or needle, placed at the bottom of a liquid pool.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, when the boundary stresses originate from surface tension, the framework of pure liquid detachment can be modified successfully and self-similar structures govern the breakup (19)(20)(21). However, in some cases the driving force comes from an alternative source, as in the case of bubble pinch-off (22)(23)(24), and self-similarity breaks down: To describe detachment, scaling laws must be used along with initial conditions.…”
mentioning
confidence: 99%